How do leading stock markets in America and Europe connect to Asian stock markets? Quantile dynamic connectedness - OlaOluwa S. Yaya; Miao Zhang; Han Xi; Fumitaka Furuoka (Quantitative Finance and Economics)
We used the quantile vector autoregressive (QVAR) dynamic connectedness framework to examine whether leading stock markets in America and Europe would have any impact on major stock markets in Asia.1 More precisely, we analyzed systematically the stock market connectedness in 15 countries, namely Germany, the UK, the USA, and 12 Asian countries, which include five major ASEAN countries, namely Indonesia, Malaysia, Philippines, Singapore, and Thailand from 1996 to 2023. The findings indicated that Hong Kong and Singaporean stocks were major transmitters of financial shocks at the extreme low price market condition, while Germany and UK were minor transmitters. By contrast, the USA could be considered the major transmitter of financial shock during the extreme high market price returns condition. In the normal market condition, these three countries in Europe and America are important transmitters of financial shock. More interestingly, the empirical findings indicated the centrality of Singapore in the stock market connectedness in Asia.